Factors associated with low-level viremia in people living with HIV: A 10-year retrospective study in South Korea - Eunmi Yang; Subin Kim; Doh Hee Kim; Mi Young Ahn; Jae-Phil Choi (PLoS ONE, 2026)
Purpose The goal of antiretroviral therapy is to achieve and sustain the suppression of human immunodeficiency virus (HIV) viral load. In this study, we aimed to identify risk factors for low-level viremia (LLV) and examine their association with clinical outcomes in South Korea. Methods We retrospectively reviewed the medical records of patients with human immunodeficiency virus infection registered at Seoul Medical Center and Hallym University Sacred Heart Hospital between 2014 and 2023. LLV was defined as at least two consecutive HIV RNA measurements of 40–199 copies/mL taken more than 4 weeks apart. Patients with LLV were compared with those who maintained virological suppression (viral load < 40 copies/mL). Results Of the 381 patients included in the analysis, 15 (3.94%) experienced LLV. Compared with patients who maintained virological suppression, patients with LLV more frequently had an initial viral load ≥ 500,000 copies/mL ( P < 0.01). No significant differences were observed between the groups in the rates of virological rebound, new-onset acquired immune deficiency syndrome–defining conditions, or mortality. Multivariable logistic regression identified an initial viral load ≥ 500,000 copies/mL as an independent risk factor for LLV (adjusted odds ratio, 4.735; 95% confidence interval, 1.505–14.897). Conclusion A high viral load was a significant risk factor for LLV. Large multicenter studies are required to further investigate risk factors and clinical implications of LLV in people living with HIV.